1992
DOI: 10.1111/j.1467-9280.1992.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Measurements in the Study of Emotion

Abstract: The study ofemotions is complicated by a number offactors, including the biological bases ofemotional experience and expression. Although biochemical changes have long been thought to be part of the e~'ocation of emotions, research has not consistently included this level of measurement, and theories of emotion have not systematically specified the role ofthese biochemical bases. In this paper, we briefly review relevant biochemical principles and m'easures that cllll be integrated into research and theory on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…11, 13 It may be that parents’ attitudes against drug use are helpful for youth, but that during drug use discussions presenting a long list of rules may threaten youth, leading to high physiological arousal, an indicator of emotional discomfort. 16 This discomfort may lead youth to avoid parents, leading to less parental supervision, association with deviant peers, and greater opportunities for substance use-although, notably, physiological reactivity was not linked to substance use in the present study. 29 Excessive focus on rules may also close off discussion about substances, leading youth to be less likely to take in helpful information from parents.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…11, 13 It may be that parents’ attitudes against drug use are helpful for youth, but that during drug use discussions presenting a long list of rules may threaten youth, leading to high physiological arousal, an indicator of emotional discomfort. 16 This discomfort may lead youth to avoid parents, leading to less parental supervision, association with deviant peers, and greater opportunities for substance use-although, notably, physiological reactivity was not linked to substance use in the present study. 29 Excessive focus on rules may also close off discussion about substances, leading youth to be less likely to take in helpful information from parents.…”
Section: Discussioncontrasting
confidence: 55%
“…It is important to examine physiological reactivity because, while a moderate level of physiological arousal may facilitate youths’ attention to parents, overly high reactivity reflects negative emotion and discomfort 16 , which may be a risk for substance use. Indeed, three studies found links between high physiological and emotional reactivity to parent-adolescent interactions and youth substance use.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important finding, given that some research has failed to find correlations across different markers of emotional arousal (Baum et al, 1992). We may have found greater convergence than past studies due to the use of personally relevant emotional stress stories, which leads to greater range of response, permitting the ability to detect associations.…”
Section: Discussionmentioning
confidence: 90%
“…Poor association between subjective and biological stress responses has previously been documented in the stress literature. There is consistent evidence of a poor association between subjective measures of anxiety and distress and HPA or catecholamine increases that commonly occur during psychological stress (Hennessey and Levine 1979;Baum et al 1992;Cohen et al 1995). This lack of direct association between the subjective and HPA and SAM responses during stress has been thought to represent the cascading effects of stress on multiple semi-independent response systems that are not necessarily causally related (Baum et al 1992;Cohen et al 1995;Lopez et al 1999).…”
Section: Discussionmentioning
confidence: 95%